Factors that Influence Consumer Interest in Choosing Online Transportation Services - Efendi, Faisal; Fiqri, Husnul; Nurlaila, Nurlaila; Candra, Afrikal; Mardianton, Mardianton; Afrinal, Afrinal (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2024)
Many interests of students of the Faculty of Economics and Business Islamic UIN IB Padang who need and use Online Transportation. To know the influence of prices, services, comfort in choosing online transportation services. This type of research uses quantitative research, which is to analyze data in numbers and process it using statistical techniques. The assumption of quantitative research is that the facts of the object of research have objective reality and that the variables can be identified and their relationships measured. The results obtained from the study can be concluded that of the Adjusted R Square value of 0.221 (41.2%). It can be interpreted that the independent variable (price, service, convenience) is 0.221 (22.1%), while the rest is influenced by other factors not included in this study variable is 0.87.8 (87.8%). From the above t test it can be concluded that the price (X1) has a sig. value (0.039) < (0.05), then partially significant influence on interest in using online transportation services. Services (X2) has a sig value (0.000) < (0.05), then partly has a significant impact on the interest to use online transportation services. Comfort (X3) has sig. (0.619) > (0.05), so partially has a significant effect on the interest in using online transit services. From the F test above it can be inferred that the Price (X1), Service (X2), Comfort simultaneously have an important influence on the value of income sig (0.001) < (0.05).